2016
DOI: 10.1080/13607863.2016.1191059
|View full text |Cite
|
Sign up to set email alerts
|

Can domestic helpers moderate distress of offspring caregivers of cognitively impaired older adults?

Abstract: These findings might suggest: a) the positive effects of audience on psychological responses to stress; b) caregiving is usually less stressful for informal caregivers not residing with care recipients. Conversely, having a domestic helper could add to caregiving distress if offspring caregivers live with their parents, most likely because offspring may witness difficulties that domestic helpers face in providing dementia care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Other research suggests that older adults, because of their established social relationships and providing care for their younger children, are less likely to commit to elderly caregiving duties [22,24]. They would rather seek external assistance in order to free up time to maintain their social lifestyles and other life commitments [13]. Higher caregiver burden, role captivity, as well as experiencing health-related lower quality of life are additional factors that have been used to explain the willingness by older adults to use external assistance [3,21,40].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other research suggests that older adults, because of their established social relationships and providing care for their younger children, are less likely to commit to elderly caregiving duties [22,24]. They would rather seek external assistance in order to free up time to maintain their social lifestyles and other life commitments [13]. Higher caregiver burden, role captivity, as well as experiencing health-related lower quality of life are additional factors that have been used to explain the willingness by older adults to use external assistance [3,21,40].…”
Section: Discussionmentioning
confidence: 99%
“…In the short term, the transition of a paid home caregiver can result in a lot of stress for the family and care recipient. In the long term, however, the paid home caregiver provides relief for the family and is a source of social support for familial caregivers [13,24,26]. Although for this partnership between the paid home caregivers and families to work, families need to guard against overloading respon-sibilities on the paid home caregiver.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, there is an increasing trend of hiring foreign domestic workers (FDWs) for this purpose in many places with developed economies [ 10 ]. This has been observed in Asia such as Taiwan [ 11 ] and Hong Kong [ 12 ], as well as in western societies, especially among some European countries [ 13 16 ]. In Singapore, this is a fairly common practice as previous studies have suggested that around half of the interviewed informal caregivers of PWDs reported that they had hired an FDW [ 2 , 4 , 17 ].…”
Section: Introductionmentioning
confidence: 97%